Ion exchange membrane, dinitrocellulosepolyaniline, cellulose, aniline, dinitrocellulose. - Bozorov, Y.Sh.; Turaev, Kh.Kh.; Djalilov А.Т.; Aliqulov, R.V.; Umbarov, I.A.; Haitov, B.T.; Akhatov, J.K.; Uralov, N.B. (Recent Contributions to Physics, 2024)
Dinitrocellulose (DNS) with a nitrogen content of 10.7-12.2% was synthesized by nitration cotton cellulose in this research work. After that, an ion exchange membrane was obtained by modifying the resulting (DNS) with aniline (AN). The resulting dinitrocellulose polyaniline (DNSPA) copolymer was dissolved in various solvents and converted into a porous ion exchange membrane by a special molding method. The obtained substances were synthesized using different mole ratios of starting substances, reaction temperature, and reaction time, and the optimal conditions of the process were determined. The produced substances were synthesized based on different applications of mole ratios of starting materials, reaction temperature, and reaction time, and the optimal conditions of the process were determined. Based on the physicochemical results of (DNSPA), its application as new ion exchange membranes was studied. In addition, the composition of the synthesized (DNSPA) was determined based on the infrared spectrum (IR-spectrum), and the element composition and surface morphology were determined based on scanning electron microscopy (SEM) and their data were presented.